Unreported truths about COVID-19 and lockdowns : Part 2 update and examination of lockdowns as a strategy - Berenson, Alex ([United States] [publisher not identified], 2020)
"From former New York Times reporter Alex Berenson, the second installment in the best-selling series that offers hard data about the coronavirus epidemic - rather than hysterical predictions of doom.While Unreported Truths Part 1 focused on how many people are dying from COVID-19, this section discusses an equally important but even more complex topic: the history of lockdowns, and the evidence that they work as intended. Like Part 1, this section draws on primary sources like Centers for Disease Control and World Health Organization reports, along with news articles, government documents, and scientific papers.In three chapters, this section explains the surprising scientific debate around lockdowns BEFORE March, along with the evidence that they did or did not work as intended to reduce the spread of the coronavirus and save lives. If you have been wondering whether lockdowns made any difference - as the media has loudly insisted - Part 2 will give you the truthful, accurate and well-sourced information you need to make up your own mind.Please note: This booklet contains only the second section of Unreported Truths. Part 1 is available separately." -- Amazon.com.
Cover title.
108530
Keywords: 2000-2099; COVID-19 (Disease); COVID-19 (Disease) -- Social aspects; Epidemics -- 21st century; Viruses -- 21st century; Public health -- 21st century